Development and introduction of new methods for determining mill capa city of boiler coalpulverization system - Мисак, Степан Йосифович (Technology audit and production reserves, 2014)
The paper gives new methods of determining the capacity of air-swept ball mills of a coal-pulverization system of coal power units of 150–200 and 300 MW, proved in production at thermal power plants (TPP). The main advantage of the methods over the known method, the disadvantage of which is the complexity of operations, manual coal selection from a conveyor belt, comparing it with subsequent calculations, is the ease and efficiency. Three methods of determining the capacity of air-swept ball mills were considered, namely: for coal-pulverization systems with industrial bunkers and a direct supply of pulverized coal to the furnace; using backup fuel. The introduction of the new methods at thermal power plants (TPP) with pulverized coal-fired boilers will give a significant economic effect due to the possibility of more effective operation of air-swept ball mills, and thus more efficient fuel combustion in boiler plant furnaces (reducing heat losses with q2 and q4) and increasing the efficiency factor (EF).